Frequency of Potential Drug–Drug Interactions in the Changing Field of HCV Therapy. (3rd February 2020) - Schulte, Benjamin; Wübbolding, Maximilian; Marra, Fiona; Port, Kerstin; Manns, Michael P; Back, David; Cornberg, Markus; Stichtenoth, Dirk O; Höner zu Siederdissen, Christoph; Maasoumy, Benjamin
Abstract: Background: With the introduction of direct-acting antivirals (DAAs) for hepatitis C virus (HCV) infection, drug–drug interactions (DDIs) emerged as significant challenge. Since then, HCV therapy and the infected population have rapidly changed. So far, very limited data are available regarding the clinical relevance of DDIs when using most modern DAA regimens. We aimed to assess how the importance of DDIs has evolved over time. Methods: From January 2014 to July 2018, 668 consecutive HCV patients were evaluated for their outpatient medication and assessed for DDIs with DAAs. Different time periods were defined based on market approval of key DAAs: A (01/2014–11/2014), B (11/2014–08/2016), and C (08/2016–07/2018). Results: The frequency of patients with real-world DDIs was highest in period B (A: 37.1%, B: 49.6%, C: 38.8%). The recently approved DAAs (period C) theoretically showed a lower DDI risk profile. However, real-world DDIs were still comparable to period A, as HCV patients' characteristics changed (eg, age ≥75 years: A: 3.1%, B: 9.8%, C: 5.6%; polypharmacy/patients with ≥8 drugs: A: 11.1%, B: 15.2%, C: 17.2%). Furthermore, although DDIs via CYP 3A4 became less important for some modern regimens, other mechanisms like an altered pH value in the stomach, causing reduced bioavailability, evolved. Relevant DDIs most frequently occurred with proton pump inhibitors, metamizole, statins, and carvedilol. Conclusions: DDIs during antiviral treatment still affect about 40% of HCV patients. The lower DDI potential of modern DAA regimens is partly counteracted by changing patient characteristics. Therefore, DDIs should not be underestimated.